"Ich will keine Nullen, sondern Bullen" Hitlers Koalitionsverhandlungen mit der Bayerischen Volkspartei im März 1933 - Dierker, Wolfgang 1968- (Vierteljahrshefte für Zeitgeschichte, 2002)
This text focuses on transcripts of meetings Bayernwacht-Führer Hans Ritter von Lex held with Hitler in March 1933 which were among church records found in the headquarters of the SD. At the end of the war, these records were confiscated by the Red Army, taken to Moscow and later transferred to the GDR where they remained locked up in the NS archives until the GDR's collapse. Today this archival material is stored in the Bundesarchiv's interim archives Dahlwitz Hoppegarten. The transcripts, which have been edited here, document discussions between Hitler and Ritter von Lex immediately after the NS takeover in Bavaria. In these meetings the possibility of a coalition government between the NSDAP and the BVP were discussed. Although the meetings were known to historians, the content and outcome of the discussions remained obscure. The transcripts reveal how Hitler, during the escalating situation of March 1933, kept several options open and made political decisions spontaneously which followed logically from the course of events. The young party leaders close to Fritz Schäffer and Ritter von Lex began a frenzied search for some middle ground between direct confrontation with the NSDAP or complete assimilation of their party convinced that maintaining political autonomy was the way. (Vierteljahrshefte für Zeitgeschichte / FUB)